A lexicon in signed language and its comprehensibility to normals - Rajalakshmi J (Journal of All India Institute of Speech and Hearing, 1970)
The present study was aimed at assessingthe usefulness of total communication with the hard of hearing children. For this purpose signed lexicon was elicited from thirty deaf students from Deaf and Blind School, Mysore, and its comprehensibility was checked on thirty normal hearing children from a local school.